Biallelic Mutations in ACACA Cause a Disruption in Lipid Homeostasis That Is Associated With Global Developmental Delay, Microcephaly, and Dysmorphic Facial Features - Lou, Xiaoting; Zhou, Xiyue; Li, Haiyan; Lu, Xiangpeng; Bao, Xinzhu; Yang, Kaiqiang; Liao, Xin; Chen, Hanxiao; Fang, Hezhi; Yang, Yanling; Lyu, Jianxin; Zheng, Hong (Frontiers in Cell and Developmental Biology, 2021)
Objective: We proposed the deficit of ACC1 is the cause of the patient symptoms including global developmental delay, microcephaly, hypotonia, and dysmorphic facial features. We evaluated the possible disease-causing role of ACACA gene in developmental delay and investigated the pathogenesis of ACC1 deficiency. Methods: The patient presented with global developmental delay with unknown cause was recruited. Detailed medical records were collected and reviewed. Whole exome sequencing founds two variants of ACACA with unknown significance. ACC1 mRNA expression level, protein expression level, and enzyme activity level were detected in patient-derived cells. Transcriptome, lipidomic analysis and in vitro functional studies including cell proliferation, apoptosis and migratory ability of patient-derived cells was evaluated to investigate the possible pathogenic mechanism of ACC1 deficiency. RNAi induced ACC1 deficiency fibroblast was established to assess the causative role of ACC1 deficit in cell migratory disability in patient-derived cells. Palmitate supplementation assays were performed to assess the effect of palmitic acid on ACC1 deficiency induced cell motility deficit. Results: The patient presented with global developmental delay, microcephaly, hypotonia, and dysmorphic facial features. A decreased level of ACC1 and ACC1 enzyme activity level were detected in patient-derived lymphocytes. Lipidomic profiles revealed a disruption in the lipid homeostasis of the patient-derived cell lines. In vitro functional studies revealed a deficit of cell motility in patient-derived cells and the phenotype was further recapitulated in ACC1-knockdown (KD) fibroblast. The cell motility deficit in both patient-derived cells and ACC1-KD were attenuated by palmitate. Conclusions: We report an individual with biallelic mutations in ACACA, presenting global development delay. In vitro studies revealed a disruption of lipid homeostasis in patient-derived lymphocytes, further inducing the deficit of cell motility capacity and the deficiency could partly attenuated by palmitate.